Kompetensi Pedagogik Guru pada Mata Pelajaran SBdP di SD Kecamatan Kembaran - Anisa Chairiyah; Okto Wijayanti (Jurnal Simki Pedagogia, 2022)
Pedagogic competence is a management ability of students which includes design, implementation of learning, and evaluation. Pedagogic competence is important for teachers and must master pedagogic competencies. Pedagogic competence is also needed in SBdP learning. Not all educators master all fields of art, only master one or a few fields of art. The purpose of this study was to determine the condition of pedagogic competence possessed by teachers, barriers and efforts to improve pedagogical competence. This research is a qualitative research with descriptive research method. Data collection techniques used are interviews, observations and documentation to 12 teachers located in 6 elementary schools, namely SD UMP, SDN Tambaksari, SDN Kembaran, SDN Linggasari 2, SDN Pliken 1 and SDN Pliken 2 with the criteria of civil servants and non-civil servants, respectively teaching in the upper and lower classes. The results of the study indicate that it is important for teachers to have pedagogical competencies. Barriers to pedagogic competence in SBdP learning are limited ability to master the three components of art, limited hours of SBdP learning, after the pandemic there was no direct interaction between teachers and students and ineffectiveness in knowing the potential and characteristics of students. Efforts to improve pedagogic competence by increasing learning about strategies and media used, knowing the potential that exists in students in SBdP learning, understanding the characteristics of students, and evaluation.